Evaluating the impact of media strategies on the educational role of new museums - Pratiwinindya, Ratih Ayu; Cahyono, Agus; Rohidi, Tjetjep Rohendi; Prameswari, Nadia Sigi (Research Journal in Advanced Humanities, 2025)
Museums as a place to promote art and culture continue to develop, so the presence of new museums (ie. Patiayam museum) certainly has branding challenges to get a large number of visitors. However, new museums have the potential to attract visitors, especially students, by offering fresh and engaging learning experiences through interactive exhibits and educational programs. The unique appeal of these museums, combined with effective promotional strategies, can spark curiosity among younger audiences and encourage school trips or group visits. A qualitative approach was employed, involving observations and semi-structured interviews to gather data from diverse informants. Accessibility, both physical and digital, was identified as a key factor influencing museum visits. Informants also highlighted the museum's educational value, emphasizing its role in providing immersive learning experiences that cater to diverse learning styles.